The efficient interfacial water evaporation enabled by a waffle-like double-network hydrogel evaporator in high-salinity seawater - Jinbu Su; Xinyu Dong; Weixin Du; Xuli Lin; Chenyi Shi; Xingxu Miao; Zifen Guo; Chengbing Wang (Desalination, 2026)

SIG-CFFNet: Structural Information-Guided Cascaded Feature Fusion Network for Gastrointestinal Anatomy Classification - Xuli Tan; Xun Gong; Lin Fan; Ting Luo (Annals of Biomedical Engineering, 2026)

Water-heat separation evaporator design for efficient solar steam generation utilizing thermal radiation-convection hybrid mechanism - Jinbu Su; Weixin Du; Yunong Xie; Xuli Lin; Chenyi Shi; Xinyu Dong; Yuyi Xu; Jing Shi; Chengbing Wang (Desalination, 2026)

Salinity-independent evaporation: Biomimetic design of large hydrogel evaporator with 3D hierarchical channels in high-salinity brine - Jinbu Su; Xuli Lin; Chenyi Shi; Xinyu Dong; Jinchi Ma; Yunong Xie; Yuyi Xu; Weixin Du; Chengbing Wang (Chemical Engineering Journal, 2025)

Aluminum-based Janus evaporator with decoupling photothermal-evaporation interfaces for enduring vapor generation - Xiaoxue Wang; Chengbing Wang; Fan Wang; Puxin Tan; Jingjing Jin; Xuli Lin; Wenhe Zhang; Zexiang Zhao; Lu Wang (Chemical Engineering Journal, 2025)

Corrigendum to “Prediction, identification, and analysis of major B-cell linear epitopes of bomb m 6 from silkworm pupa” [Food Chemistry 463 (Part 2) (2025) 141211] - Wenqi Yue; Songyuan Huang; Shiwen Lin; Xue Feng; Li Yan; Zhencong Yang; Zhoujin Xu; Xuli Wu (Food Chemistry, 2025)

Marangoni-driven regional salt crystallization for high salinity desalination - Jinbu Su; Xuli Lin; Jinchi Ma; Chenyi Shi; Yunong Xie; Haizhou Xu; Yuyi Xu; Xinyu Dong; Weixin Du; Xiaoyu Cao; Chengbing Wang (Chemical Engineering Journal, 2025)

Marangoni-driven regional salt deposition in self-cleaning paper based evaporators for stable and high-performance desalination - Yunong Xie; Jinbu Su; Weixin Du; Chenrui Ji; Kuangtaibei Zhang; Jilun Wang; Yuyi Xu; Xuli Lin; Chenyi Shi; Xinyu Dong; Chengbing Wang (Chemical Engineering Journal, 2025)

Prediction, identification, and analysis of major B-cell linear epitopes of bomb m 6 from silkworm pupa - Wenqi Yue; Songyuan Huang; Shiwen Lin; Xue Feng; Li Yan; Zhencong Yang; Zhoujin Xu; Xuli Wu (Food Chemistry, 2025)

A 3D Janus-like structure evaporator based on capillary force promoting efficient solar steam generation - Yunong Xie; Jinbu Su; Chenrui Ji; Yuyi Xu; Xuli Lin; Chenyi Shi; Weixin Du; Xinyu Dong; Chengbing Wang (Desalination, 2025)

High-performance Chinese ink flower-shaped evaporator: Intensified heat through light concentration to achieve water-energy balance - Jinbu Su; Yunong Xie; Heng Zhao; Yuyi Xu; Xuli Lin; Chenyi Shi; Xiaoyu Cao; Chengbing Wang (Chemical Engineering Journal, 2024)

Janus MXene-based photothermal membrane for efficient and durable water evaporation - Jinbu Su; Yunong Xie; Pengkui Zhang; Rui Yang; Boli Wang; Heng Zhao; Yuyi Xu; Xuli Lin; Jing Shi; Chengbing Wang (Desalination, 2023)

Genome-wide identification and functional characterization of borneol dehydrogenases in Wurfbainia villosa - Xiaojing Lin; Linxuan Huang; Huilin Liang; Chen Hou; Xuli Ling; Yuanxia Chen; Peng Yang; Qingwen Wu; Haiying Zhao; Sirong Wu; Ruoting Zhan; Dongming Ma; et al. (Planta, 2023)

Modulating the allergenicity and functional properties of peanut protein by covalent conjugation with polyphenols - Weiyi He; Kan He; Xiaoyu Liu; Liying Ye; Xiao Lin; Li Ma; Pingchang Yang; Xuli Wu (Food Chemistry, 2023)

Aggravation of food allergy symptoms by treatment with acrylamide in a mouse model - Jiamin Chen; Liuying Li; Liying Ye; Xiao Lin; Songyuan Huang; Wenqi Yue; Xuli Wu (Food and Chemical Toxicology, 2023)

Natural forests promote phosphorus retention in soil - Zhen Yu; Zhou Guoyi; Lei Liu; Stefano Manzoni; Philippe Ciais; Daniel Goll; Josep Peñuelas; Jordi Sardans; Wantong Wang; Jie Zhu; Lin Li; Junhua Yan; et al. (Global Change Biology, 2022)
Soil phosphorus (P) availability often limits plant productivity. Classical theories suggest that total P content declines at the temporal scale of pedogenesis, and ecosystems develop toward the efficient use of scarce P during succession. However, the trajectory of ecosystem P within shorter time scales of succession remains unclear. We analyzed changes to P pools at the early (I), middle (II), and late (III) stages of growth of plantation forests (PFs) and the successional stages of natural forests (NFs) at 1969 sites in China. We found significantly lower P contents at later growth stages compared to earlier ones in the PF ( p p